MACROECONOMIC ASPECTS OF AGRI-ENVIRONMENTAL MEASURES IN THE EU - Popović, Goran (Economics of Agriculture, 2009)
Economic growth and social progress are unthinkable without the use of natural resources. Their exploatation in the previous decades was mostly accelerated, unplanned and often followed by the devastation of the environment. Modern theories of economic growth give the great importance to mitigation of this problem. Policy of sustainable development find its place more and more in the economies of the developed countries. Impossibility of the states to appropriate the larger part of the GDP for the sustainable development is the biggest drag on its full affirmation. The EU member countries also meet with this problem. There is the political will for soloving the problem on protection of the environment in the EU, but it is subject to the need of maintaining the macroeconomic balance and preservation of the external competitiveness. This approach is even more tightened in the times of crises and recesions. However, the EU has the long time measures of the environment protection out of which the agri-environmental measures are extremly significant. They are realized at the level of the EU and at the national levels. Can the agro-environmental measures give the macroeconomic impulses and at what level? That's why the agri-environmental measures in the economic terms have the keynesian character. The other benefit is the increase of the land prices, as the territories under the agri-environmental measures become more expensive in the course of time, what is significant for the future investitors. Work confirms the limited macroeconomic activity of the agri-environmental measures as the significant positive externality of the EU.